Turkey’s Industry 4.0 Adventure: Dream or Realization - Tecim , Vahap; Tarhan, Cigdem (KnE Social Sciences, 2020)
Today’s technology minimizes human errors and enables the implementation of applications that will enable electronic devices to work flawlessly as much as possible. Both socially and technically, in each sector with all levels, the manager must make decisions based on his/her responsibility and interest. In these environments, making the right decision, unprotected or minimal damage to the risks, depends on the personal ability of the decision-maker as well as the information that comes with it. The concept of Industry 4.0, which has emerged in parallel with technological developments, includes the transformation of production and service activities into modern automation systems in social areas and the use of new methods in data exchange. In this context, the internet of the objects, the internet of services and cyber-physical systems constitute the basic structures of the new formation. In this study, the use of these technologies in the areas where social sciences operate in the fields of which are the components of the technological developments that emerged as Industry 4.0 are discussed in the topics of Autonomous Robots, Big Data, Simulation, System Integration, Cyber Security, Cloud Computing, 3D Printers, Enhanced and Virtual Reality. Planning, analysis, design, coding and implementation stages of many technologies produced and implemented by Management Information Systems for social sciences with the reason of the emergence of Industry 4.0, innovation, flexibility and efficiency approach will be explained in this study. Additionally, this paper examines the effect of the industrial transformation in Turkey. Keywords: Industry 4.0, internet of things, management information systems, information technologies